Prediction of Inadequate Bowel Preparation Using Total and Segmental Colon Transit Time in Patients with Chronic Constipation: Some Different Outcomes - Chunying Zhai; Qiyang Huang; Ningli Chai; Wengang Zhang; Enqiang Linghu (Gastroenterology Research and Practice)
Aims. Radio-opaque markers have been widely used in the study of colon motility in patients with chronic functional constipation (FC). Here, we evaluate the relationship between the colon transit time (CTT) and the Boston Bowel Preparation Scale (BBPS) to determine whether CTT is a sufficient predictor of bowel preparation in patients with chronic functional constipation. Methods. A total of fifty-six patients with constipation and fifty-two healthy controls (HC) were enrolled in this study. All subjects underwent the colonic transit study using radio-opaque markers and were given a follow-up colonoscopy examination on day 3 to 7 to determine BBPS. The correlation between total and segmental CTT and BBPS was evaluated, and risk factors for predicting inadequate bowel preparation were determined. Results. In our study, we found some distinct outcomes compared with previous studies. The mean total CTT (TCTT) was determined to be 43.37±18.82 h in the FC group and 23.08±10.18 h in the HC group. This difference was found to be significant for both the total and segmental CTTs between the two groups (P<0.05). Further, TCTT was negatively correlated with BBPS both in the FC (r=−0.899, 95% CI -0.748 to -0.925, P<0.001) and the HC (r=−0.978, 95% CI -0.854 to -1.003, P=0.004) groups, as was segmental CTTs and segmental BBPS (P<0.05). In the case of patients with slow transit constipation, multivariate logistic regression analysis indicated that prolonged TCTT (OR 0.722, 95% CI 0.589-0.885, P=0.002) was independently associated with poor bowel preparation. The total and right to left CTTs were found to predict inadequate bowel preparation and exhibited the best sensitivity and specificity at 48.0 h, 15.5 h, 17.5 h, and 19.0 h, based on ROC curve analysis. Conclusions. The CTT test represents a valuable method for predicting the level of bowel preparation prior to a colonoscopy examination. That is, both total and segmental CTTs can be considered an objective predictor of bowel preparation prior to colonoscopy. The present study demonstrates some distinct results relative to previous studies, including STC subtype proportion in FC, the proportion of inadequate bowel preparation in the STC subtype, and the cut-off value of TCTT for predicting inadequate bowel preparation.